ELT STUDENTS’ ETHICAL CHALLENGES THROUGH THE LENS OF SOCIAL EMOTIONAL LEARNING (SEL) - Zulida, Evi; Jamilah, Jamilah; Ciptaningrum, Dyah Setyowati (Universitas Islam Sumatera Utara (UISU), 2025)
In increasingly multicultural English Language Teaching (ELT) settings, ethical concerns are not merely pedagogical but also emotional and interpersonal. The study here explores the ethical challenges for undergraduate ELT learners and looks at how Social Emotional Learning (SEL) abilities play a role in overcoming these challenges. Taking the qualitative case study approach, data were collected through semi-structured interviews, reflective journals, and observations of classrooms of 20 students of English Language Education Study Program Universitas Samudra. On the basis of thematic analysis, three broad categories of ethical issues academic integrity, group conflict, and cultural tensions were analysed through the framework of SEL including self-awareness, social awareness, relationship skills, and responsible decision-making. Results indicate that students possessing higher SEL abilities resolved moral dilemmas in more positive manners, while students without such abilities tended to use avoidance or feel emotional distress. The study highlights an urgent need to integrate SEL values into ELT instruction to create ethical consciousness and emotional resilience in students. Implications are reform in teacher preparation, course redesign, and ongoing cross cultural examination of ethics and emotional development in language learning contexts.